AKTIVITAS ANTIBAKTERI FRAKSI SAPONIN DARI KULIT BATANG TUMBUHAN KASTURI (Mangifera casturi) - K. Rosyidah; S. A. Nurmuhaimina; N. Komari; M. D. Astuti (Universitas Lambung Mangkurat, 2010)
This research to study antibacterial activity (E.coli and S.aureus) of saponin fractions from stem bark of Mangifera casturi. Powdered of stem bark of M.casturi (512,67 g) were extracted with methanol. Methanol extract (32.57 g) was partitionated with n-hexane to give saponin extract. Saponin extract (5.98 g) was partitionated by Vacuum Liquid Chromatography (VLC) over silica gel to give 39 fractions were grouped into four major fractions A-D by combining fractions with similar TLC profile. Every fractions studied antibacterial activity with E. coli and S. Aureus with difusi methode. Fraction A most active then other fraction with inhibition diameter 10.3 ± 0.5 mm (E.coli) and 10.8 ± 0.3 mm (S.aureus).